2009
DOI: 10.1158/1078-0432.ccr-08-2755
|View full text |Cite
|
Sign up to set email alerts
|

Protumorigenic Role of HAPLN1 and Its IgV Domain in Malignant Pleural Mesothelioma

Abstract: Purpose Tumor extracellular matrix (ECM) plays a crucial role in cancer progression mediating and transforming host-tumor interactions. Targeting the ECM is becoming an increasingly promising therapeutic approach in cancer treatment. We find that one of the ECM proteins, HAPLN1, is overexpressed in the majority of mesotheliomas. This study was designed to characterize the protumorigenic role of HAPLN1 in mesothelioma. Experimental Design Overexpression of HAPLN1was assessed and validated on a large set of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 43 publications
3
36
0
Order By: Relevance
“…Transfection media were removed after 4 h of incubation and replaced with fresh Dulbecco's modified Eagle's medium, 10% fetal bovine serum medium. 48 h post-transfection, miR-31-transfected cells were trypsinized, counted, and assayed for proliferation, colony formation in soft agar, wound closure, and Matrigel invasion in triplicate experiments as described previously (16,17).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transfection media were removed after 4 h of incubation and replaced with fresh Dulbecco's modified Eagle's medium, 10% fetal bovine serum medium. 48 h post-transfection, miR-31-transfected cells were trypsinized, counted, and assayed for proliferation, colony formation in soft agar, wound closure, and Matrigel invasion in triplicate experiments as described previously (16,17).…”
Section: Methodsmentioning
confidence: 99%
“…Validation of Putative miR-31 Targets-For clinical validation of putative miR-31 targets, we used our U133 Plus 2.0 Affymetrix expression array data from 32 MM and 7 normal peritoneal specimens as described previously (10,16). Western analysis was performed with antibodies to PPP6C (NB100-2883) and MCM2 H00004171-M01) from Novus Biologicals (Littleton, CO).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell motility, migration, invasion and colony formation in soft agar Scratch (wound healing) assay was performed as described, 69 following the inhibition of proliferation using mitomycin C at 5 mg/ml. Migration and invasion assays used 8.0 mm polycarbonate membrane inserts for 24-well plates (BD Biosciences, Franklin Lakes, NJ, USA).…”
Section: Azd7451mentioning
confidence: 99%
“…Takashima et al reported proteomic analysis of AAbs in patients with hepatocellular carcinoma using autologous tissues and sera, but did not focus on AAbs derived from a tumor-associated stroma (28). Solid tumors are composed of neoplastic cells and surrounding tumor-associated stroma, and the latter is essential for the survival and proliferation of tumor cells (10). The invasion of cancer cells into surrounding tissues is the hallmark of malignancy, and the invasion process is associated with the marked destruction and regeneration of stromal elements, composed of inflammatory cells, including lymphocytes, granulocytes, and macrophages, vascular endothelial cells and pericytes, and fibroblasts (9).…”
mentioning
confidence: 99%